A hole transport layer and its preparation method and its application in quantum dot light emitting diode
The polymer hole transport layer prepared by photocrosslinking uses crosslinking agents containing bisbenzophenone and alkyl (oxygen) chains to form a three-dimensional network structure, which solves the problems of low surface energy of the polymer hole transport material film and interlayer erosion, and significantly improves the performance of QLED devices.
Patent Information
- Application Number
- CN202110684777.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-06-21
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-06-21
AI Technical Summary
In the prior art, the surface energy of the film prepared by polymer hole transport materials is low, resulting in poor spread of the upper luminescent layer solution. Due to the good solubility of the organic solvent, interlayer erosion is prone to occur, affecting the stability and performance of the QLED device.
The hole transport layer is prepared by photocrosslinking using a polymer hole transport material and a crosslinking agent containing bisbenzophenone and alkyl (oxygen) chains. The structural formula of the crosslinking agent is: where R is, m and p are independently selected from natural numbers greater than or equal to 1, and a three-dimensional network structure is formed by photocrosslinking to achieve complete solvent resistance of the hole transport layer.
The excellent solvent resistance and high surface energy of the hole transport layer are achieved, the interface stability and hole injection effect of the film are improved, and the overall performance of QLED devices is significantly improved, including maximum current efficiency, maximum power efficiency and external quantum dot efficiency.
Smart Images

Figure CN113675354B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optoelectronic materials, and in particular relates to a hole transport layer and a preparation method thereof, and application thereof in quantum dot light emitting diodes. Background Art
[0002] The flat panel display industry is an important part of the development of the national economy. Among them, organic light-emitting diodes have entered the mass production stage, but they are mainly prepared by vacuum evaporation, which has the problems of low material utilization, poor product yield and high cost. However, printing display technology, which has the advantages of simple preparation process, high material utilization and large-scale production, is considered to be one of the best technical choices for large-size flat panel displays in the future. It is worth noting that quantum dot light-emitting diodes (QLEDs) using inorganic quantum dot materials have attracted much attention from the industry and academia because of their narrow emission spectrum, high color purity and wide color gamut, and can be fully solution-printed to produce thin and flexible display devices.
[0003] In the research and development process of QLED device preparation by spin coating (inkjet printing), the most commonly used hole transport materials are polymers TFB, poly-TPD and PVK. However, the surface energy of the film prepared by this type of polymer hole transport material is relatively low, which is not conducive to the spreading of the upper light-emitting layer solution; in addition, since the polymer hole transport material has good solubility in common organic solvents, and the solvents used to prepare the quantum dot light-emitting layer, such as toluene and chlorobenzene, are also good solvents, corrosion often occurs between the prepared film layers, which is not conducive to the preparation of a stable device interface. Although the orthogonal solvent method can prepare high-performance QLED devices, it is relatively difficult to find a suitable orthogonal solvent and has great limitations on the material system. The above problems have seriously affected the preparation of high-performance QLED devices by the solution method (inkjet printing) and restricted the industrialization process of QLED.
[0004] The literature Nanoscale Horiz., 2017, 2, 156-162 reported that TFB and BP-BP crosslinker containing benzophenone group were bonded under 365nm light conditions to prepare a hole transport layer with solvent resistance. The reaction route is as follows:
[0005]
[0006] Although the hole transport layer obtained by the above method is solvent-resistant and has the advantages of simple method and readily available materials, the external quantum efficiency of the QLED device prepared based on the hole transport layer is low and the device performance is not ideal. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a hole transport layer that is solvent-resistant and can obtain excellent device performance and a preparation method thereof.
[0008] The second object of the present invention is to provide a use of the above hole transport layer in a quantum dot light emitting diode.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] A hole transport layer is prepared by photo-crosslinking a polymer hole transport material and a crosslinking agent, wherein the molecular structure of the polymer hole transport material has at least Group, the structural formula of the cross-linking agent is: In the formula, R is Wherein, m and p are independently selected from natural numbers greater than or equal to 1.
[0011] According to some implementation aspects of the present invention, the cross-linking agent has the structural formula:
[0012] Wherein, 2≤m≤20. When the hole transport layer prepared by the crosslinking agent is used to prepare a device, as m gradually increases, the overall performance of the device is first improved and then decreased. Preferably, m is greater than or equal to 2 and less than or equal to 10. More preferably, m is selected from 4, 5, 6, 7, and 8. When m is selected from 6, it is most conducive to improving the performance of the device.
[0013] According to other embodiments of the present invention, the cross-linking agent has the structural formula:
[0014] Wherein, 1≤p≤10. When the hole transport layer prepared by the crosslinking agent is used to prepare a device, as p gradually increases, the overall performance of the device will tend to decrease. Preferably, the p is selected from 1, 2, 3, 4, and 5. More preferably, the p is selected from 1, 2, and 3. When the p is selected from 1, it is most conducive to improving the performance of the device.
[0015] According to some embodiments of the present invention, the polymer hole transport material is a polymer and / or Wherein, n and x are independently selected from natural numbers greater than or equal to 1.
[0016] The hole transport layer prepared with the polymer TFB and / or poly-TPD and the cross-linking agent effectively overcomes the solvent resistance of the polymer hole transport material (TFB or poly-TPD), achieves a solvent resistance of the hole transport layer greater than or equal to 98%, or even 100%, and effectively avoids the problem of interlayer corrosion.
[0017] The TFB and poly-TPD are existing commercialized hole transport materials.
[0018] According to some implementation aspects of the present invention, the photocrosslinking is performed under irradiation of ultraviolet light with a wavelength of 365nm; or, the photocrosslinking is performed under irradiation of ultraviolet light with a wavelength of 365nm and a temperature of 50-80°C. The wavelength of 365nm is relatively long, and the degree of damage to the performance of the formed material film is extremely low, and the electrical and optical properties of the original polymer hole transport material can be inherited or even surpassed.
[0019] According to some embodiments of the present invention, the photocrosslinking uses a wavelength of 365 nm and a power of 100 mW / cm 2 UV light.
[0020] According to some implementation aspects of the present invention, the photocrosslinking time is 10 to 120 minutes.
[0021] According to some implementation aspects of the present invention, the mass ratio of the polymer hole transport material to the crosslinking agent is 5 to 40:1.
[0022] The cross-linking method using ultraviolet light or a combination of ultraviolet light and heating does not require the addition of additional photoinitiators or catalysts, and the reaction time for achieving complete cross-linking is short and there are no by-products in the reaction process.
[0023] The second technical solution adopted by the present invention is: a method for preparing the hole transport layer described above, the preparation method comprising dissolving the polymer hole transport material and the crosslinking agent in an organic solvent, forming a thin film by spin coating or inkjet printing, and then obtaining the hole transport layer by photocrosslinking.
[0024] According to some embodiments of the present invention, the organic solvent is a combination of one or more of toluene, m-xylene, methyl benzoate, chlorobenzene, o-dichlorobenzene, cyclohexylbenzene, indene, and anisole.
[0025] The third technical solution adopted by the present invention: an application of the hole transport layer described above in a quantum dot light emitting diode.
[0026] The fourth technical solution adopted by the present invention: a quantum dot light emitting diode, comprising the hole transport layer described above.
[0027] Furthermore, the quantum dot light-emitting diode comprises an anode layer, a hole injection layer, the hole transport layer, a quantum dot light-emitting layer, an electron transport layer and a cathode layer which are arranged in sequence.
[0028] In some embodiments, the anode layer is made of tin oxide (ITO); the hole injection layer can be formed by spin coating poly (3,4-ethylenedioxythiophene) (PEDOT) and polystyrene sulfonate (PSS); the electron transport layer is made of Zn y Mg 1-y O, wherein 0<y<1; the cathode layer is made of Al.
[0029] According to some implementation aspects of the present invention, the quantum dot light emitting diode further includes a substrate, and the anode layer is disposed on the substrate.
[0030] In some embodiments, the substrate is glass.
[0031] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0032] The hole transport layer of the present invention is prepared by photocrosslinking a crosslinking agent containing a bisbenzophenone group and an alkyl (oxy) chain and a polymer hole transport material having a bis(4-phenyl)(4-butylphenyl)amine group. The crosslinking agent contains an electron-rich alkoxy group and has higher photosensitivity. The obtained hole transport layer has higher performance. It not only has excellent solvent resistance, but also can effectively improve the interface stability of the film, improve the hole injection effect and electron blocking ability, effectively improve the device performance, and obtain more excellent device performance. Compared with the existing device prepared by using BP-BP as a crosslinking agent, the performance is more excellent.
[0033] The hole transport layer of the present invention is prepared by photocrosslinking a crosslinking agent containing a bisbenzophenone group and an alkyl (oxy) chain with a polymer hole transport material having a bis(4-phenyl)(4-butylphenyl)amine group. Compared with the existing method using BP-BP as a crosslinking agent, the hole transport layer has a larger surface energy and better spreadability, is more conducive to the spreading of the upper layer solution on its surface, is more suitable for an inkjet printing preparation process with very high requirements for spreadability, and has great application prospects.
[0034] The hole transport layer of the present invention has excellent solvent resistance, and achieves compactness and high stability of the hole transport interface, thereby effectively improving the efficiency and life of the QLED device. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Schematic diagram of the ultraviolet absorption spectra of the film in Example 1 before cross-linking and after cross-linking and chlorobenzene cleaning;
[0036] Figure 2 A schematic diagram of an atomic force microscope of the film prepared in Example 1;
[0037] Figure 3 A three-dimensional (3D) microscope schematic diagram of the film prepared in Example 1;
[0038] Figure 4 Schematic diagram of the ultraviolet absorption spectra of the film in Example 2 before cross-linking and after cross-linking and chlorobenzene cleaning;
[0039] Figure 5 Schematic diagram of the ultraviolet absorption spectra of the film in Example 5 before cross-linking and after cross-linking and chlorobenzene cleaning;
[0040] Figure 6 Schematic diagram of the structure of a QLED device;
[0041] Figure 7 Schematic diagram of the current density-voltage-luminance (JVL) characteristic curves of red light QLEDs devices using TFB alone and using BP6 and TFB cross-linked anti-solvent hole transport layer.
[0042] Figure 8 Schematic diagram of the power efficiency-luminance-current efficiency (PE-L-CE) characteristic curves of red light QLEDs devices using TFB alone and using BP6 and TFB cross-linked anti-solvent hole transport layer.
[0043] Fig. 9 Schematic diagram of the external quantum dot efficiency-brightness (EQE-L) characteristic curves of red light QLEDs devices using TFB alone and using BP6 and TFB cross-linked anti-solvent hole transport layer.
[0044] Fig.10 The electroluminescence spectra of red light QLEDs devices using TFB alone and using BP6 and TFB cross-linked anti-solvent hole transport layer. DETAILED DESCRIPTION
[0045] The inventors combine a polymer hole transport material TFB or poly-TPD with a crosslinker containing a benzophenone group under ultraviolet light or ultraviolet light combined with heating. The crosslinker captures the hydrogen atoms in the active CH in the amine group under ultraviolet light irradiation, and forms a hole transport layer with a three-dimensional network structure through a free radical coupling reaction, thereby achieving complete solvent resistance of the hole transport layer, avoiding interlayer corrosion problems in QLED devices, and forming a more stable device interface. In addition, the crosslinker used in the present invention will also effectively improve the surface energy of the hole transport layer, facilitate the spreading of the upper solution, and achieve high-quality spin coating (printing) of multi-layer QLED devices.
[0046] The structural formula of the crosslinking agent is:
[0047] In the formula, R is m and p are independently selected from natural numbers greater than or equal to 1.
[0048] The cross-linking principle is as follows:
[0049]
[0050] Among them, when the polymer hole transport material is poly-TPD, the reaction sites are not limited to those shown in the above formula. In the poly-TPD molecular chain, all The hydrogen atoms in the active CH of the amine-containing groups on the repeating unit can be captured by the cross-linking agent.
[0051] Below in conjunction with specific embodiment, further set forth the present invention.Should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.In addition should be understood that, after reading content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall equally within the scope of the appended claims of the application.
[0052] The structural formula of BP4 is: Wherein, m is 4.
[0053] The structural formula of BP6 is: Wherein, m is 6.
[0054] The structural formula of BP8 is: Wherein, m is 8.
[0055] Example 1 (Preparation of a hole transport layer using BP6 and TFB)
[0056] The solvent-resistant hole transport layer provided in this embodiment is prepared by the following method:
[0057] BP6 and TFB were mixed in a mass ratio of 1:10 to prepare an 8 mg / mL chlorobenzene solution, which was then spun on the substrate at 3000 rpm for 30 seconds. The solution was annealed at 120°C for 10 minutes, and then cross-linked for 30 minutes under ultraviolet light (365 nm) and heated at 60°C for 15 minutes. After cross-linking and annealing, the solution was allowed to stand for half an hour to fully cool, and the cross-linked film was washed with toluene and chlorobenzene in turn.
[0058] UV-visible absorption spectroscopy was used to study the changes in the UV absorption intensity of the film before cross-linking and after cross-linking and chlorobenzene cleaning, so as to clearly determine whether it was eroded by the solvent. Specifically, the UV absorption intensity of the film before cross-linking (i.e., the film formed by spin coating the chlorobenzene solution of BP6 and TFB on the substrate and not irradiated with UV light and heated) was tested; the cross-linked film (i.e., the film irradiated with UV light and heated) was washed with toluene and chlorobenzene in turn, and the UV absorption intensity of the film was tested again after the solvent dried. Figure 1The absorption intensity of the film before cross-linking and after cross-linking and chlorobenzene washing is basically unchanged, indicating that 100% cross-linking is achieved and the hole transport layer film has excellent solvent resistance.
[0059] The surface of the cross-linked film was characterized by atomic force microscopy and 3D-microscopy. Figure 2 and Figure 3 As shown, through Figure 2 It can be seen that the root mean square roughness of the cross-linked film is as low as 0.97nm, indicating that its surface roughness is very low and the film surface is relatively smooth. Figure 3 It can be seen that the entire film exhibits good flatness. The film formed by cross-linking TFB and BP6 has a good film morphology and forms a relatively stable interface layer, which is conducive to the spreading of the upper solution.
[0060] Example 2 (Preparation of hole transport layer using BP6 and poly-TPD)
[0061] The solvent-resistant hole transport layer provided in this embodiment is different from that in Example 1 in that BP6 and poly-TPD are mixed in a mass ratio of 1:6 to prepare a 10 mg / mL chlorobenzene solution, which is spun on the substrate at a speed of 3000 rpm for 30 seconds, annealed at 120°C for 10 minutes, and then cross-linked for 30 minutes under ultraviolet light (365 nm) and heating at 60°C for 15 minutes. After cross-linking and annealing, the film is allowed to stand for half an hour to fully cool, and then the cross-linked film is washed with toluene and chlorobenzene in turn.
[0062] UV-visible absorption spectroscopy was used to study the changes in the UV absorption intensity of the films before cross-linking and after cross-linking and chlorobenzene cleaning, such as Figure 4 The absorption intensity of the film before cross-linking and after cross-linking and chlorobenzene washing is basically unchanged, indicating that 100% cross-linking is achieved and the hole transport layer film has excellent solvent resistance.
[0063] Example 3 (Preparation of hole transport layer using BP4 and TFB)
[0064] The solvent-resistant hole transport layer provided in this embodiment is different from that in Embodiment 1 in that BP4 is used instead of BP6, and the rest is the same as in Embodiment 1.
[0065] Example 4 (Preparation of a hole transport layer using BP8 and TFB)
[0066] The solvent-resistant hole transport layer provided in this embodiment is different from that in Embodiment 1 in that BP8 is used instead of BP6, and the rest is the same as in Embodiment 1.
[0067] Example 5 (Preparation of a hole transport layer using BP1O and TFB)
[0068] The solvent-resistant hole transport layer provided in this embodiment is different from that in embodiment 1 in that: BP10 is used. Replace BP6, and the rest is the same as Example 1.
[0069] UV-visible absorption spectroscopy was used to study the changes in the UV absorption intensity of the films before cross-linking and after cross-linking and chlorobenzene cleaning, such as Figure 5 shown.
[0070] Comparative Example 1
[0071] The hole transport layer provided in this comparative example is different from that in Example 1 in that: Replace BP6, and the rest is the same as Example 1.
[0072] The surface energy of the hole transport layer films prepared in Examples 1 to 4 and Comparative Example 1 was tested, and the surface energy of the hole transport layer films prepared using TFB and poly-TPD alone was tested. The results are shown in Table 1.
[0073] Table 1 shows the surface energy test results of various hole transport layer films
[0074]
[0075] When the surface tension of the quantum dot solvent does not change, the larger the surface energy of the solid film, the more conducive it is to the spreading of the solution on its surface. As can be seen from Table 1, the introduction of the crosslinker BP6 significantly increases the surface energy of the solvent-resistant hole transport layer film. Compared with the uncrosslinked TFB film, poly-TPD and the film formed by BP-BP crosslinking in the literature, it is more conducive to the spreading of the upper layer solvent and is suitable for the inkjet printing preparation process with high requirements for spreading.
[0076] Application Example 1 (Preparation of Device by Spin Coating)
[0077] Based on the preparation of the hole transport layer mentioned above, QLED devices were prepared by spin coating and inkjet printing. The device structure was: ITO (160nm) / PEDOT:PSS (30nm) / HTL (25nm) / QDs (15nm) / Zn x Mg 1-x O(5nm) / Al(100nm), such as Figure 6 shown.
[0078] The device is specifically prepared by the following method:
[0079] The ITO glass was scrubbed with glass cleaner, ultrasonically cleaned with water and ethanol in turn, and treated with oxygen plasma for 5 minutes. PEDOT:PSS was statically spin-coated on the ITO surface at a speed of 4000 rpm for 30 seconds. After the spin coating was completed, the ITO sheet was transferred to a glove box and annealed at 130°C for 15 minutes; then, the hole transport layer was spin-coated, and a mixed solution of the hole transport material and the cross-linking agent (such as the chlorobenzene solution of TFB and BP6 in Example 1) was dynamically spin-coated at a speed of 3000 rpm for 30 seconds, and then annealed at 140°C for 15 minutes after spin coating, and then cross-linked for 30 minutes under ultraviolet light (365nm) and 60°C heating for 15 minutes, and then stood for half an hour to fully cool after cross-linking annealing. Spin-coated quantum dot luminescent material was dynamically spin-coated on the hole transport layer at a speed of 3000 rpm for 30 seconds; after the spin coating was completed, annealed at 100°C for 5 minutes and stood for 2 to 3 minutes to cool. Dynamic spin coating of Zn at 3000 rpm 0.9 Mg 0.1 O solution, anneal at 70℃ for 15 minutes. After all the solution treatment layers are made, the wafer is transferred to a high vacuum thermal evaporation device to evaporate the top electrode aluminum. The evaporation rate is 3-5 angstroms / second, and the electrode thickness is 100 nanometers. After the evaporation is completed, it is encapsulated with UV curing glue.
[0080] By adopting the preparation method of the above device, different hole transport materials are used to prepare different hole transport layers, and then different red light QLED devices are prepared, and the performance of the red light QLED devices is tested.
[0081] Figure 7 A schematic diagram showing the current density-voltage-luminance (JVL) characteristic curves of red QLEDs devices using TFB alone and using BP6 and TFB cross-linked anti-solvent hole transport layers; Figure 8 A schematic diagram of the power efficiency-luminance-current efficiency (PE-L-CE) characteristic curves of red QLEDs devices using TFB alone and using BP6 and TFB cross-linked anti-solvent hole transport layers; Fig. 9 A schematic diagram showing the characteristic curves of the external quantum dot efficiency-brightness (EQE-L) of red light QLEDs devices using TFB alone and using BP6 and TFB cross-linked anti-solvent hole transport layers; Fig.10 The electroluminescence spectra of red light QLEDs devices using TFB alone and using BP6 and TFB cross-linked anti-solvent hole transport layer are shown.
[0082] The performance of the red light QLED devices with different hole transport layers prepared are summarized, and the results are shown in Table 2.
[0083] Table 2 summarizes the performance of red QLED devices with different hole transport layers.
[0084]
[0085] As can be seen from Table 2, compared with the red light QLED devices prepared by commercial TFB or poly-TPD polymer hole transport materials, the BP-based m The solvent-resistant hole transport layer of BP1O (m is 4, 6 or 8) and TFB or poly-TPD can effectively improve the interfacial stability of the film, improve the hole injection effect and electron blocking ability, and the overall performance of the prepared QLED device has been significantly improved, with the maximum current efficiency reaching 32.0 cd A -1 , the maximum power efficiency reaches 32.6lm W -1 , the maximum external quantum dot efficiency reached 20.5% (an increase of 83%), and its half-peak width and color coordinates were 100% inherited. It is worth noting that the present invention found that in BP m Among the series of cross-linkers, the cross-linked hole transport layer based on BP6 is most conducive to improving the performance of QLED devices.
[0086] Application Example 2 (Preparation of Device by Inkjet Printing)
[0087] The structure of the device is the same as that of the device in Application Example 1, and the preparation method of the device is different from that in Application Example 1 in that the quantum dot light-emitting layer is prepared by inkjet printing, and the rest is the same as that in Application Example 1. The device performance is shown in Table 3.
[0088] Table 3 is a comparison of the performance of devices prepared by spin coating and inkjet printing for quantum dot light-emitting layers
[0089]
[0090] Note: The hole transport layer of the device is the hole transport layer prepared by the method of Example 1.
[0091] As can be seen from Table 3, the maximum external quantum efficiency EQE of the device obtained by preparing the quantum dot light-emitting layer by inkjet printing reaches 18.2%. Compared with the device obtained by spin coating the quantum dot light-emitting layer, the maximum external quantum efficiency can achieve nearly 90% of the device performance of the spin coating device.
[0092] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
[0093] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
Claims
1. A hole transport layer, prepared by photo-crosslinking a polymer hole transport material and a crosslinking agent, wherein the polymer hole transport material has at least A group characterized by: The structural formula of the cross-linking agent is: Among them, 2≤m≤20, 1≤p≤10; The polymer hole transport material is polymer TFB and / or poly-TPD Wherein, n and x are independently selected from natural numbers greater than or equal to 1.
2. The hole transport layer according to claim 1, characterized in that: The m is greater than or equal to 2 and less than or equal to 10.
3. The hole transport layer according to claim 1, characterized in that: The m is selected from 4, 5, 6, 7, and 8.
4. The hole transport layer according to claim 1, characterized in that: The p is selected from 1, 2, 3, 4, and 5.
5. A method for preparing a hole transport layer according to any one of claims 1 to 4, characterized in that: The preparation method comprises dissolving the polymer hole transport material and the crosslinking agent in an organic solvent, preparing a thin film by spin coating or inkjet printing, and then obtaining the hole transport layer by photocrosslinking.
6. Use of the hole transport layer described in any one of claims 1 to 4 in a quantum dot light emitting diode.
7. A quantum dot light emitting diode, characterized in that: A method of manufacturing a hole transport layer comprising the hole transport layer according to any one of claims 1 to 4.
Citation Information
Patent Citations
Method for preparing electroluminescent device through laminating method
CN107425143A
Photosensitive crosslinking agent and preparation method and application thereof
CN107602886A